Anxiety Mediates the Link Between Psychopathy and Aggression in NGRI Acquittees. (June 2021) - Thomson, Nicholas D.; Kevorkian, Salpi; Galusha, Carla; Wheeler, Elizabeth M. A.; Ingram, Lindsay
Psychopathy has been long associated with anxiety, and anxiety has been argued to play an important role in psychopathy-related behaviors, such as aggression. However, these associations have not yet been explored in Not Guilty by Reason of Insanity (NGRI) Acquittees. The goals of the present study were to test the correlations between the 4-facet psychopathy construct and anxiety, and to assess whether anxiety mediates the association between psychopathy and aggression. In a sample of 81 NGRI acquittees, anxiety was positively related to the lifestyle facet. When testing the mediating role of anxiety on the psychopathy-aggression link, the results showed that low anxiety mediated the link between the interpersonal facet and aggression. By contrast, high anxiety mediated the link between the lifestyle facet and aggression. These results highlight the disparate associations between specific psychopathy features and anxiety in predicting aggressive behavior. The present findings demonstrate that violence reduction strategies may need to become more tailored to individual needs when it comes to reducing risk among people with varying levels of psychopathic traits and serious mental illness.